Bio-Polyurethane Resins Derived from Liquid Fractions of Lignin for the Modification of Ramie Fibers - Manggar Arum Aristri; Muhammad Adly Rahandi Lubis; Raden Permana Budi Laksana; Faizatul Falah; Widya Fatriasari; Maya Ismayati; Asri Peni Wulandari; Nurindah (Department of Forestry, Faculty of Agriculture, University of Lampung, 2021)
Lignin is a biopolymer from agro-forestry biomass which provides greater prospects for higher added value applications in renewable and sustainable products. In this study, technical lignin from black liquor was used as a pre-polymer for the preparation of bio-polyurethane (Bio-PU) resins. Briefly, the isolated lignin was fractionated using ethyl acetate (EtAc) and methanol (MeOH). The liquid fractions of lignin, such as lignin-EtAc (L-EtAc) and lignin-methanol (L-MeOH), were mixed with 10% of polymeric isocyanate (based on the weigth of liquid fractions) to obtain Bio-PU resins. The isolated lignin, fractionated lignin, and lignin-derived Bio-PU resins were characterized using several techniques. The obtained Bio-PU resins then were used to modify ramie fibers using vacuum impregnation method. Fourier Transform Infrared (FTIR) spectroscopy, Differential Scanning Calorimetry (DSC), and Thermogravimetric Analysis (TGA) revealed that the isolated lignin had quite similar characteristics to lignin standar. Fractionation of lignin with EtAc and MeOH altered its characteristics. FTIR, DSC, and TGA showed that solid fractions of lignin had similar characteristics to lignin standard and isolated lignin, while the liquid fractions had characteristics from lignin and the solvents. The absorption band of isocyanate (-N=C=O) groups was shifted to 2285 cm-1 from 2240 cm-1 owing to the reaction with the -OH groups in lignin, forming urethane (R-NH-C=O-R) groups at 1605 cm-1 in Bio-PU resins. Thermal properties of Bio-PU resins derived from L-EtAc exhibited greater endothermic reaction compared to Bio-PU-L-MeOH. As a result, the free -N=C=O groups in Bio-PU resins have reacted with -OH groups on the surface of ramie fibers and improved its thermal properties. Modification of ramie fibers with Bio-PU resins improved the fibers' thermal stability by 15% using Bio-PU-LEtAc for 60 min of impregnation. Keywords: bio-polyurethane resins, impregnation, lignin fractions, ramie fibers, thermal stability